Faith Schools: Consensus or Conflict (June 27-28, 2002 • Institute of Education, London, UK THURSDAY 27 JUNE 2002) (American Journal of Islam and Society, 2002)
Opening Speech: Lord DearingLorcl Dearing (C. of E.) gave an overview of the Dearing Report, publishedin June 2001. He reminded the audience that historically, education hasbeen rooted in faith. The influence of the state has been increasingly feltsince 1870. He raised the issues of what justifies faith schools and distinguishesthem from others. He covered the arguments of spiritual/moral educationprovision; and parental wish. He commented that parents look tofaith schools for their discipline, caring attitude and security of values.When discussing the academic achievement argument, he commented thatGCSE results in faith schools are 12% higher than in non faith schools,which still made them more attractive, if not spectacularly so.He stressed that recently, faith schools have been urged to be inclusive.They should respect people of other faiths and challenge those of no faith.Ultimately, the outcome of faith schools is measured by the quality ofhuman beings they educate.Faith Schools: Consensus or Conflict?Keynote Speech by Professor Richard Pring (University of Oxford)Richard Pring (Catholic) stated in his introduction that there was a paradoxin the fact that 33% schools in the UK are faith schools when 45% peopleclaim to have no faith. He reviewed the arguments for faith schools: higheracademic standards, including in disadvantaged communities, although theNFER research qualifies this evidence; diversity; choice: the issue is ratherwhat are the aims we seek to promote?; ethos/value system; equality of treatment,although this could easily be reversed and lead to the abolition of allfaith schools; parents v. State, cf.. "Education is too important to be put inthe hands of the State." Pring considers the argument of academic excellence ...